The Shadow of Koentjaraningrat: Anthropology in Indonesia’s Post-Colonial - Reza Imawan, Zinedine (CV. Era Digital Nusantara, 2024)
Abstract: This paper aims to explore the development of Koentjaraningrat's thoughts and his role in establishing the anthropology discipline in Indonesia. Through a comprehensive literature review of books, journals, articles, and reports, this paper traces Koentjaraningrat's intellectual journey and the evolution of anthropology within the country. The findings reveal that Koentjaraningrat was a pivotal and consistent intellectual figure who not only laid the foundation for anthropology in Indonesia but also contributed significantly to nation-building through an anthropological framework. This paper aims to elaborate on the development of Koentjaraningrat's ideas, which emerged in the context of Indonesia’s decolonization and the influence of American intellectual traditions. Purpose: The aim of this study is to explore the development of Koentjaraningrat's thoughts in the context of establishing the anthropology discipline in Indonesia. Design/Methodology/Approach: his study uses literature review to examine books, journals, articles, and reports detailing Koentjaraningrat's intellectual journey and the development of anthropology in Indonesia. Findings: The findings reveal that Koentjaraningrat was a consistent intellectual figure who not only built the anthropology discipline in Indonesia but also contributed to nation-building through the anthropological framework. Originality/value: Examining the development of Koentjaraningrat’s thoughts that evolved amidst Indonesia’s decolonization and American intellectual traditions.